«The Shanghai Life»: a Source-Study Review - Sun Yizhi (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the source study of «The Shanghai Life», its dissemination outside China and current collection situation. Due to the absence of this newspaper in the collections of Shanghai archives and libraries, information about its collection in archives, libraries and museums of other countries is relevant for both Chinese and Russian researchers. For several years, the author of this article has been trying to gather the most complete collection of issues of this newspaper and to reconstruct a comprehensive picture of the history of the newspaper’s dissemination outside China, to know the current collection situation of this newspaper in various libraries, archives and museums around the world.